The Influence of Health Promotion on the Incidence of Measles in Children: A Systematic Review - Supriyadi Supriyadi; Eti Rimawati; Vilda Ana Veria Setyawati (PSPP JOURNALS, 2026)
Measles, an infectious disease, remains a serious health problem throughout Indonesia. The government has provided an effective and affordable vaccine, but immunization coverage remains low, contributing to the increase and high number of measles cases in Indonesia. One contributing factor is maternal knowledge about immunization and other contributing factors. Health promotion is an effort to improve maternal knowledge. This systematic review aims to find evidence based on published articles related to health promotion and the factors contributing to measles incidence. The criteria for this study were original articles and respondents located in Indonesia, with articles published between 2020 and 2025. The review method used was PRISMA, obtained from databases such as PubMed, Google Scholar, and Scient Direct. The review resulted in 15 articles out of 1,223 selected articles. Measles incidence is influenced by maternal factors, child factors, immunization compliance, and promotional media used. Conclusion: The role of health promotion significantly influences individuals' knowledge and decision-making regarding immunization of their children.